2016
DOI: 10.1016/j.jtcme.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger powder supplementation on nitric oxide and C-reactive protein in elderly knee osteoarthritis patients: A 12-week double-blind randomized placebo-controlled clinical trial

Abstract: There is limited evidence that ginger (生薑 shēng jiāng) powder consumption can relieve pain and inflammation because of its special phytochemical properties. This study is aimed at investigating the effect of ginger powder supplementation on some inflammatory markers in patients suffering from knee osteoarthritis. This is a double-blind randomized placebo-controlled clinical trial with a follow-up period of 3 months that was conducted on 120 outpatients with moderately painful knee osteoarthritis. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 25 publications
(24 reference statements)
3
56
0
Order By: Relevance
“…Naderi et al conducted a 12-week clinical trial to investigate the effects of ginger supplementation on nitric oxide and CRP in elderly knee osteoarthritis patients and reported that ginger powder supplementation at a dose of 1 g/d can reduce inflammatory markers in patients with knee osteoarthritis (5), which is in line with the findings of a study by Rahimlou et al (35). However, one study reported that after oral administration of 100–1,000 mg/ml squeezed ginger extract in mice, the production of inflammatory markers increased (16).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Naderi et al conducted a 12-week clinical trial to investigate the effects of ginger supplementation on nitric oxide and CRP in elderly knee osteoarthritis patients and reported that ginger powder supplementation at a dose of 1 g/d can reduce inflammatory markers in patients with knee osteoarthritis (5), which is in line with the findings of a study by Rahimlou et al (35). However, one study reported that after oral administration of 100–1,000 mg/ml squeezed ginger extract in mice, the production of inflammatory markers increased (16).…”
Section: Discussionsupporting
confidence: 53%
“…C-reactive protein (CRP) is a plasma protein that rises in the systemic response to inflammatory conditions (3); in addition, there is a link between elevated level of this protein and major cardiovascular events (4, 5). Interleukin-6 (IL-6) is an important inflammatory cytokine that induces the hepatic production of CRP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that ZO powder supplementation (1 g/day) for 3 months can reduce the serum level of nitric oxide and high-sensitivity reactive protein hs-CRP in patients with knee OA. The inflammatory markers started to decrease after 3 weeks of treatment [96]. Several other studies showed clinical improvement in OA patients with ZO extract, as evaluated by the pain score with VAS, reduction in intake of rescue medication, having mostly mild gastrointestinal adverse events, and similar or even better efficacy and satisfaction score than the standard treatment prescribed by the orthopedic specialist [97][98][99].…”
Section: Zingiber Officinalis Fam Zingiberaceaementioning
confidence: 98%
“…Ginger powder exhibited significant reduction in arthritis index and visual analog scale scores and it is attributed to reduced production of NO and CRP. [58,59] 6-shagoal is most potent antioxidant and anti-inflammatory agent among other shagaols and gingerols. [60] Ginger essential oil, a secondary metabolite of ginger, also prevented chronic joint inflammation, and granuloma formation.…”
Section: Shagoalmentioning
confidence: 99%